Outcome of Two Corneal Collagen Crosslinking Methods in Bullous Keratopathy due to Fuchs’ Endothelial Dystrophy - Omur O. Ucakhan; Ayhan Saglik (Case Reports in Medicine)
Four eyes of 2 patients with corneal edema due to Fuchs’ endothelial dystrophy were treated with CXL using the standard protocol. Since no improvement in visual acuity, corneal clarity, thickness, or pain sensation was evident in any eye at month 12, 2 eyes of the 2 patients were retreated, this time, following intraoperative corneal dehydration with glycerol 70% drops. This retreatment also failed to produce any significant effect on vision, corneal clarity, thickness, or pain in either eye. Collagen crosslinking with the current protocols may not be effective in the management of eyes with corneal edema due to Fuchs’ endothelial dystrophy. Further studies are required to establish the efficacy of CXL and optimize the technique and/or dehydration method utilized in these cases.